The effect of "fusafungine" on the incidence of upper respiratory tract symptoms in ultradistance runners - Kiessig, Michael; Kiessig, Michael (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Fusafungine is an antibiotic of fungal origin with a potent local anti-inflammatory action (German-Fattal, 1995; German-Fattal, 1996). It is administered locally to the nasal and pharyngeal mucosa by spray. It can be hypothesised that the anti-inflammatory action of fusafungine may decrease the development of mucosa! inflammation in such a manner that the incidence of symptoms of upper respiratory tract infection may be reduced if it is administered before, during and after completion of an ultramarathon. Furthermore, fusafungine could also reduce the risk of secondary bacterial infection. The potential value of fusafungine in reducing the symptoms of upper respiratory tract infections or the development of bacterial upper respiratory infection is the focus of this thesis.